2017
DOI: 10.1093/nutrit/nux011
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a tolerable upper intake level of niacin: a systematic review and meta-analysis of the dose-dependent effects of nicotinamide and nicotinic acid supplementation

Abstract: Results may indicate a high degree of conservativeness in the UL of nicotinic acid, fixed at 35 mg/d in United States and 10 mg/d in Europe. Reconsideration of the UL of nicotinic acid for nutritional supplements, possibly differentiating between ULs in healthy and unhealthy individuals, may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Second, the use of wild type mice may also prove the potential benefits of niacin and/or fatty acids in HFDs in a non‐genetically modified cohort. From a translational point of view and given the undesirable flushing at therapeutic doses of niacin, it is probable that an HFD in wild type mice could be the most appropriate control in a study design that did not involve niacin.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the use of wild type mice may also prove the potential benefits of niacin and/or fatty acids in HFDs in a non‐genetically modified cohort. From a translational point of view and given the undesirable flushing at therapeutic doses of niacin, it is probable that an HFD in wild type mice could be the most appropriate control in a study design that did not involve niacin.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggesting that high dietary niacin intake may be associated with osteoporosis is in contrast with the concept that there are no adverse effects from naturally occurring niacin from food . In agreement with the idea that dietary intake of niacin needs to be considered with respect to disease states, a recent meta‐analysis suggested that the limits of nicotinic acid for nutritional supplements should be reconsidered, and that appropriate limits may differ for healthy versus disease states . Our findings in CHS suggest that trials including niacin intake for diseases of the aging, in particular, studies including patients at high risk for fracture, should include assessments of BMD and incident fractures and measure concentrations of niacin to understand more about the apparently complex association of niacin with BMD and osteoporosis, with careful consideration of different levels of dietary intake of niacin.…”
Section: Discussionmentioning
confidence: 99%
“…It is a trace nutrient known as vitamin B3 (Lanska, 2012), available in certain foods (dairy products, fish, eggs, and vegetables) (Minto et al, 2017), nutritional supplements and fortified foods (Colbourne et al, 2013). Its effects are associated with energy metabolism and neuroprotection (Chi and Sauve, 2013).…”
Section: Precursors Of Nad +mentioning
confidence: 99%